Stereotactic ablative radiation therapy for operable early-stage lung cancer—considerations and controversies - Daniels, Christopher P.; Moghanaki, Drew; Siva, Shankar (Therapeutic Radiology and Oncology, 2019)
Stereotactic ablative radiation therapy (SABR) is the current standard of care for patients with stage I non-small cell lung cancer (NSCLC) who are not fit for surgery or who refuse an operation. The available evidence suggests that SABR is effective in obtaining durable local control in operable patients as well, but whether it can currently be recommended as an alternative to surgery in this population is contentious because of the absence of high quality long-term prospective randomized survival data. Retrospective comparisons of SABR with surgery are available, but have been subject to bias from the confounding effect of operability. Previous attempts to prospectively compare SABR with surgery in a randomized fashion have been unsuccessful due to poor accrual. From these efforts, the randomized data from two of these prematurely closed trials were combined to explore the potential outcome if they had completed accrual, though the analyses were largely dismissed by the academic community. In this review, we give a critical overview of the available data in this context, and address key areas of controversy which include the questioned importance of pathologic staging of the mediastinum, the appropriate thresholds for empiric treatment of suspicious lung nodules without biopsy confirmation, and the challenges of post-treatment surveillance of the irradiated lung. We also address design considerations aimed at maximising enrolment into ongoing prospective phase III trials of SABR versus surgery.